Economic Emergence Depends upon Positive Health Condition of Masses: A Study with Special Reference to the Effects of Wrong use of Drugs on Human Health that Impacts Economic Output - Sreemoyee Ghosh; Farida Isroani; Sanchita Saha (JOURNAL OF SHARIA ECONOMICS, 2023)
ealth improvement is indeed a significant social priority because good human capital condition improves the abilities, efficiency, and quality of life of a workforce. Thus, it is important to understand the factors pertaining to the Economic output of an individual in a group context. Illness, whether it is physical or mental, can have a negative impact on the economic output of an individual in an organization. Positive mental and physical health makes a person productive, whereas negative mental health makes a person unproductive even if the person is physically healthy. The Micro and Macro environment of the workplace also play a pivotal role in the productive output of an individual. Hence, we need to get a delighted mind in a favorable workplace with a healthy and composed physical entity in order to contribute to the domain of work towards the accomplishment of the objective of the work. The effects of illness and disease burden lead to loss of productivity, social isolation or exclusion and a negative socio-economic spiral for the individual as well as for the collective. Medicines play a crucial role in the healthcare industry as they are the compounds which are having direct or indirect impact on human health. However, wrong use or abuse of medicines in any way proves detrimental to the mental and physical health of the person. So, it is also essential to understand the relation of use of medicine for disease control and productivity. This will lead to right and rational use of medicine which in turn will help the domain of economy on a positive scale. On the other hand, for getting a delighted mind at the workplace, an individual must be freed from the lower order emotions and egoistic identities which lead to disvalues. Rather, a person, who can maintain a life with higher consciousness through a sustained effort of union with the supreme, can be elevated to a state of mind which is desireless and that desireless action can lead to optimum productivity.